Respuesta :

Answer:

x=-37

Step-by-step explanation:

First, rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation:

                    2*x-31-(3*(x+2))=0

(2x - 31) -  3 • (x + 2)  = 0

Pulling out like terms

3.1     Pull out like factors :

  -x - 37  =   -1 • (x + 37)

Equation at the end of step

 -x - 37  = 0

Solving a Single Variable Equation:

4.1      Solve  :    -x-37 = 0

Add  37  to both sides of the equation :

                     -x = 37

Multiply both sides of the equation by (-1) :  x = -37

ACCESS MORE